Wavefunction engineering towards high-performance terahertz quantum cascade lasers - Seyed Ghasem Razavipour (Scientific Reports)
Abstract In the quest for high-performance terahertz (THz) quantum cascade lasers (QCLs), this study introduces a generalized wavefunction engineering approach to efficiently control state populations at elevated temperatures. Analyzing known two-well structures and their limitations, a three-well QCL design based on a direct depopulation scheme is proposed. Employing a combination of rate equations-density matrix and NEGF modelings, our design achieves superior performance at 290 K by simultaneously optimizing injection coupling, thermal back-filling, and electron escape rates from upper and lower lasing states to parasitic states.